A study on the grief process of bereaved family members of terminally ill patients of selected municipalities in Region 8. - Bornillo, Vic Marie L., et al.; Gerale, Ian Earl Shieldon L.; Villafranca, Ruby Anne G. (Tacloban City Vic Marie L. Bornillo, Ian Earl Shieldon L. Gerale [and] Ruby Anne G. Villafranca, 2010)
This is a descriptive study which aims to understand the self-evaluation of 16 bereaved family members of selected municipalities in Region 8 whose loved ones died because of terminal illness. Besides, it also shows how these families coped with and took actions with regards to the patients' health conditions.
A qualitative method was used by the researchers in analyzing the data gathered. The most common reactions of the family members upon knowing that their loved ones were diagnosed with terminal illness were shock and depression. However, almost all of them had already accepted the death of their loved ones and live life again by the support of others and with a healthy lifestyle.
The researchers have found out that in spite of the tragedy that the family had gone through they consider it as a learning experience which helped them cultivate a more resilient personality and well-being. In fact, happiness which is thought to be the opposite attitude of bereavement is observed among bereaved family members of terminally ill patients. They also consider themselves as more optimistic and resilient than before.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science